2020
DOI: 10.1590/1516-4446-2018-0400
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin decreases cocaine-induced locomotor activity in pinealectomized rats

Abstract: Objective: Several studies have shown that the time of day regulates the reinforcing effects of cocaine. Additionally, melatonin and its MT 1 and MT 2 receptors have been found to participate in modulation of the reinforcing effects of such addictive drugs as cocaine. Loss of the diurnal variation in cocaine-induced locomotor sensitization and cocaine-induced place preference has been identified in pinealectomized mice. In addition, several studies in rodents have shown that administration of melatonin decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Based on our findings, we would predict that females raised in Long photoperiod would exhibit more sign-tracking behavior than males or females raised in other photoperiods. Such studies would be especially pertinent as evidence suggests that substance use disorders show seasonality as well (Sandyk and Kanofsky, 1992;Sher, 2004;Morales-Muñoz et al, 2017;Barbosa-Méndez and Salazar-Juárez, 2020).…”
Section: Long Photoperiod Enhances Dat Inhibition In Femalesmentioning
confidence: 99%
“…Based on our findings, we would predict that females raised in Long photoperiod would exhibit more sign-tracking behavior than males or females raised in other photoperiods. Such studies would be especially pertinent as evidence suggests that substance use disorders show seasonality as well (Sandyk and Kanofsky, 1992;Sher, 2004;Morales-Muñoz et al, 2017;Barbosa-Méndez and Salazar-Juárez, 2020).…”
Section: Long Photoperiod Enhances Dat Inhibition In Femalesmentioning
confidence: 99%
“…Many studies have also claimed that melatonin has a strong neuroprotective effect against glutamate-induced excitotoxicity (Espinar et al, 2000 ; Lima et al, 2003 ; Vishnoi et al, 2016 ). Recently, melatonin has been shown to attenuate the rewarding behavior associated with many drugs of abuse such as cocaine (Sircar, 2000 ; Barbosa-Mendez and Salazar-Juarez, 2020 ) and alcohol (Vengeliene et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory action of melatonin on enhanced dopamine release was first demonstrated in excised female rat hypothalamic tissue in vitro, and it appears to be mediated by membranal, low-affinity melatonin binding sites by suppression of calcium influx into the stimulated nerve endings 77 . Melatonin inhibits dopamine release in the retina and mesencephalic dopamine areas 78 . It was reported that melatonin enhanced norepinephrine content in the adrenal medulla of chronically stressed rats 79 .…”
Section: Discussionmentioning
confidence: 99%